2022
DOI: 10.3389/fcell.2021.762029
|View full text |Cite
|
Sign up to set email alerts
|

Immune Infiltration in Gastric Cancer Microenvironment and Its Clinical Significance

Abstract: Immunotherapy has developed rapidly and has gradually become one of the important methods for treatment of gastric cancer (GC). The research on tumor infiltrating immune cells (TIICs) and immune-related genes in the tumor microenvironment (TME) greatly encourages the development of immunotherapy. The devolution algorithm (CIBERSORT) was applied to infer the proportion of 22 TIICs based on gene expression profiles of GC tissues, which were downloaded from TCGA and GEO. TCGA was utilized to analyze the different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…Tumors with enriched TAMs infiltrate would represent advanced stages of GC in full progression and be virtually resistant to the host's immune system. A number of previous studies have explored the immune microenvironment of gastric cancer through TCGA and GEO databases, showing a similar trend to our results, which validate our CyTOF data well (43,44). Other studies identified several prognosis-related genes and further constructed a prognostic model of gastric cancer patients based on public databases (45)(46)(47)(48)(49).…”
Section: Discussionsupporting
confidence: 89%
“…Tumors with enriched TAMs infiltrate would represent advanced stages of GC in full progression and be virtually resistant to the host's immune system. A number of previous studies have explored the immune microenvironment of gastric cancer through TCGA and GEO databases, showing a similar trend to our results, which validate our CyTOF data well (43,44). Other studies identified several prognosis-related genes and further constructed a prognostic model of gastric cancer patients based on public databases (45)(46)(47)(48)(49).…”
Section: Discussionsupporting
confidence: 89%
“… 61 Moreover, systematic reviews of gene expression profiles in patient biopsies revealed the importance of immune infiltration as an indicator for patient prognosis and a predictive factor for immunotherapy in gastric cancers. 62 , 63 Consistent with the aforementioned preclinical studies, the positive effects of oxaliplatin-based immunogenic (neoadjuvant) chemotherapy on the immune microenvironment has been confirmed by the meta-analysis of in silico data, as well as by multiplex immunostaining and next-generation sequencing (NGS) of gastric cancer biopsies, 64 altogether showing an elevated level of CTLs in the tumor immune infiltrate of patients treated with oxaliplatin, correlating with improved objective response rates. More direct proof for the synergistic effect of oxaliplatin and ICI therapy comes from the recent clinical trial CheckMate 649 65 targeting unresectable gastric and gastro-esophageal junction carcinomas.…”
Section: Main Textmentioning
confidence: 52%
“…Macrophages in the tumor microenvironment predominantly exhibit an M2 phenotype with high CD163 expression [ 36 , 37 ]. M2 macrophages play a crucial role in promoting gastric cancer progression and metastasis and suppressing immune reactions in the tumor microenvironment, revealing a poor prognosis in tumors with increased M2 macrophage infiltration [ 10 , 37 ]. CD8 T lymphocytes are considered to perform important functions in anti-tumor reactions, and several studies have shown an improved prognosis in gastric cancers with a high density of CD8 T lymphocytes [ 10 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…M2 macrophages play a crucial role in promoting gastric cancer progression and metastasis and suppressing immune reactions in the tumor microenvironment, revealing a poor prognosis in tumors with increased M2 macrophage infiltration [ 10 , 37 ]. CD8 T lymphocytes are considered to perform important functions in anti-tumor reactions, and several studies have shown an improved prognosis in gastric cancers with a high density of CD8 T lymphocytes [ 10 , 38 ]. In contrast, other studies revealed contradictory results, showing worse survival in patients with high intra-tumoral CD8 T lymphocyte density, and suggested that the effects of CD8 T lymphocytes on cancer cells are dependent on the histopathological features of cancer cells and other immune factors in the tumor microenvironment, such as programmed death-ligand 1 (PD-L1) expression [ 35 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation